Partial oxidation of synthesized wastewater containing lignin to vanillin and phenol under mild conditions - Sriprom, Pongsert; Leephisuth, Pornyamon; Neramittagapong, Arthit; Neramittagapong, Sutasinee (My University, 2020)
Partial oxidation of synthesized wastewater containing lignin to form phenol and vanillin was investigated. The reactions were carried out in a high-pressure reactor at various temperatures in the range of 140–200 ° C and under the air atmosphere with the initial air pressure of 2 bar for 75 min. The addition of NaOH has a strong effect on the formation of vanillin and phenol. The results showed that the highest vanillin concentration of 23.4 ppm and the highest phenol production of 30 ppm were obtained at a temperature of 140 °C and 200 °C, respectively. The vanillin and phenol can be produced from the partial oxidation of wastewater containing lignin at mild conditions.
Keywords: Hydrothermal; Phenol; Vanillin; Waste management